Spreading The Spirit of The American Dream Through Walt Disney’s Film “Meet The Robinsons” - Ratini Setyowati (IAIN Salatiga, 2012)
This article is aimed to know about the spirit of American dream and its influences. The study is a qualitative study using library research and the data were obtained from texts. The data are analyzed and presented descriptively. The researcher finds that The American Dream has influenced people around the world because America has very effective ways to promote their ideology through soft power “five big ideas”. The power is more powerful than military power. Meet the Robinson has been a provocative film; it can be media to promote the spirit of the American Dream.Keywords: The American Dream; Soft power ;five big ideas